DIVISIBILITY CRITERIA FOR SOME PRIME NUMBERS - A.Z. Khalilov; Sh. A.Xaydarov (Western European Studies, 2024)
In this paper, we have considered the proofs of the numbers 7, 13, 17, 19, 23, 29 and examples of the division signs
Keywords: Number theory; last digit; remainder; integer numbers